PENGARUH MEDAN MAGNET DENGAN JARAK PEMASANGAN PADA SELANG BAHAN BAKAR TERHADAP EFISIENSI KOMPOR GAS LPG - Agus Harianto; Makinun Makinun; Heri Santoso (Universitas Lambung Mangkurat, 2016)
LPG gas stove is a tool used to convert the chemical energy of fuel into heat energy that is used for the cooking process. The use of magnetic can be affect efficiency of LPG gas stoves. The purpose of this study to determine the influence of the magnetic field and the distance of the installation of the fuel lines to the efficiency of LPG gas stove, so that can be seen optimal location of installation of magnets on the fuel line. Variations installation from the stove inlet is 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, and 120 cm. In this study, using a magnetic 5000 gauss. The observed data is the fuel consumption, cooking time savings and efficiency. The results of this study indicate that the installation of magnets in the fuel hose at a distance of 60 cm from the stove inlet is the most optimal with an efficiency of 55%. So that compared with a standard stove without magnet there is an increased efficiency of 89.65%.